Efektivitas Video Edukasi terhadap Pengetahuan Remaja Putri tentang Sadari di SMP Negeri 6 Pekanbaru - Yena, Indah Rahma; Hayati, Susani (Universitas Pahlawan Tuanku Tambusai, 2025)
Breast cancer is the most prevalent type of cancer in Indonesia, with reported cases reaching 65,858. Early detection can be performed through breast self-examination (BSE), known locally as SADARI. This study aimed to evaluate the effectiveness of educational videos in improving female students’ knowledge of BSE at SMP Negeri 6 Pekanbaru. A quantitative approach was employed using a pre-experimental design with a One-Group Pretest–Posttest format. The study sample consisted of all 200 eighth-grade students selected through a total sampling technique. Data were collected using questionnaires and analyzed with the Wilcoxon test. The findings revealed that prior to the intervention, 53% of students had poor knowledge of BSE; however, after viewing the educational video, the average knowledge level improved significantly, with 75% demonstrating good knowledge. The Wilcoxon test, at a 5% significance level (α = 0.05), yielded a Z-value of -14.107 and an asymptotic significance (2-tailed) of 0.000, which is less than α, leading to the rejection of the null hypothesis (H0). In conclusion, educational videos are effective in enhancing female students’ knowledge of BSE at SMP Negeri 6 Pekanbaru. It is recommended that SMP Negeri 6 Pekanbaru utilize video media as instructional material related to breast health to further improve students’ awareness and knowledge.